THE EFFECT OF APPLYING THE TEAM QUIZ LEARNING MODEL ON STUDENT ECONOMIC LEARNING OUTCOMES ON MATERIAL CLASS X FINANCIAL SERVICES INSTITUTIONS PUBLIC HIGH SCHOOL 2 PADANG BOLAK - Sari, Erlina; Kubtiyah Ritonga, Mariyatul; Hasanah, Siti (Qawwam : The Leader's Writing, 2025)
This study aims to determine the effect of the application of the Team Quiz learning model on the learning outcomes of Economics students in Financial Services Institution materials in Class X of SMA Negeri 2 Padang Bolak. In particular, this study wants to know: (1) the effect of the application of the Team Quiz learning model; (2) comparison of student learning outcomes before and after the application of the model; and (3) the extent to which the Team Quiz learning model has a significant influence on improving learning outcomes. This study is an experimental research with a population of 53 students and a sample of 25 students who were randomly selected through the lottery method. The data collection technique uses observation and learning outcome tests. The results of the hypothesis test showed that the value of t-count = 9.669 was greater than the t-table = 1.711, with a significance value (sig. 2-tailed) = 0.001 < 0.05. Thus, an alternative hypothesis (Hₐ) is accepted, which means that there is a significant influence between the application of the Team Quiz learning model on students' Economics learning outcomes in Financial Services Institution materials in Class X of SMA Negeri 2 Padang Bolak.